2021
DOI: 10.4049/immunohorizons.2000112
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Acute Lung Injury by a Novel CD14-Inhibitory Receptor Activator of the NF-κB Ligand Peptide in Mice

Abstract: Although CD14 has been implicated in the initiation of multiple TLR-mediated inflammatory responses to sepsis and sepsis-related acute lung injury (ALI), an inhibitor of CD14, except for neutralizing Abs, has not been developed. A partial peptide, microglial healing peptide 1 with N-terminal acetylation and C-terminal amidation (MHP1-AcN), derived from the receptor activator of the NF-rB ligand, was recently found to inhibit multiple TLR signaling in the macrophages. Therefore, we hypothesized that the inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…companies' focus areas. Specifically, we have shown the efficacy of MHP1 in psoriasis 21) (in which TLR7 and TLR8 are involved in the pathogenesis of psoriasis), lung fibrosis, and acute lung injury models 19) (in which TLR2, TLR4, and TLR9 are related to the pathogenesis of these lung-related disorders). Through these experiments, we expanded the scope of therapeutic applications of MHP1 and elucidated the mechanism by which MHP1 suppresses TLR signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…companies' focus areas. Specifically, we have shown the efficacy of MHP1 in psoriasis 21) (in which TLR7 and TLR8 are involved in the pathogenesis of psoriasis), lung fibrosis, and acute lung injury models 19) (in which TLR2, TLR4, and TLR9 are related to the pathogenesis of these lung-related disorders). Through these experiments, we expanded the scope of therapeutic applications of MHP1 and elucidated the mechanism by which MHP1 suppresses TLR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Some degraded products contain active moieties with antiinflammatory effects 18) , suggesting that the degraded peptides may have anti-inflammatory effects. Subsequent studies have revealed that MHP1 also acts on CD14, a TLR co-receptor, and inhibits the binding of TLR2, 4, 7, and 9 ligands to TLRs, thereby suppressing the expression of multiple proinflammatory cytokines 19) (Figure 2). In a mouse model of transient middle cerebral artery occlusion, MHP1 infiltrated only the infarcted area after intravenous infusion, and continuous subcutaneous infusion improved neurological symptoms for up to 8 h after the onset of ischemic stroke.…”
Section: Development Of Rankl Partial Peptide Mhp1 (Microglial Healin...mentioning
confidence: 99%
“…Injection of recombinant human CD14 in lean and obese mice has also been found to result in sepsis independent changes in adipose cell expression of metabolic genes. Interestingly, CD14 ‐deficient mice subjected to high‐fat diet are more resistant to obesity, insulin resistance and cardiovascular disease [65]. Subsequently, CD14 has been shown to regulate SIRT1 activity, a master regulator of metabolism [66].…”
Section: Cd14 In Human Diseasesmentioning
confidence: 99%
“…Western blotting and immunostaining were performed, as described previously. 16 See the Supplemental Material for details.…”
Section: Western Blottingmentioning
confidence: 99%